The use of virtual reality in a large scale industry project - Olofsson, Thomas; Woksepp, Stefan; Jongeling, Rogier (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2005)
LKAB, a large mining company in Sweden, has decided to invest in a new pelletizing plant in Malmberget, Sweden (MK3). The total expenditure will amount to €280 million and the new plant is expected to be operational around the turn of the year 2006-2007. Contractors are expected to employ about 250 in connection with the construction of the plant, while some 150 consultants and engineers are engaged in the design phase. Since time to market is a crucial factor for LKAB, the contractual agreements for cooperation in the project support collaborative working methods such as concurrent engineering, open information flow and introduction of innovations in the design process. The complexity of the project, the number of actors involved and the desire to involve end users such as industrial workers responsible for the future plant operations in the design makes VR an excellent enriched source of communication in the review process. Godkänd; 2005; 20061230 (ysko)